FEATURES OF MIGRATION FLOWS OF KOREANS TO RUSSIA IN THE 19TH CENTURY: QUANTITATIVE AND QUALITATIVE CHARACTERISTICS - Ravshanovna, Shodieva Vazira (Journal of Learning on History and Social Sciences, 2024)
This article examines the characteristics of Korean migration to the Russian Empire in the 19th century. Based on the analysis of historical sources and modern research, the main quantitative and qualitative characteristics of migration flows, reasons for resettlement, and the impact of this process on the socio-economic development of the Russian Far East are identified.